A Chinese Birth Cohort: Theoretical Implications - Friday, Paul C.; Ren, Xin; Weitekamp, Elmar G. M.; Kerner, Hans-Jürgen; Taylor, Terrance J. (Journal of research in crime and delinquency, 2005)
Research on delinquency has shown consistent results across Western industrialized countries. Few studies have been done in non-Western cultures. This study reports on the results of a birth cohort study in China, which was started by Marvin Wolfgang but never completed. The cohort, born in 1973, was traced through official and community files. The amount of delinquency is significantly low. However; significant differences were found between delinquents and nondelinquents in terms of peer influences, family influences, and school. Regression results show that the most important school factors associated with offending are those relating to level of education completed and dropout status and interactions between students and teachers. Offenders were found to be approximately five times more likely than nonoffenders to associate with delinquent peers. This study reinforces previous findings-there are critical sociological variables related to social integration, family, and school experiences that significantly differentiate between those who become offenders and those who do not. ABSTRACT FROM AUTHOR